1994
DOI: 10.1007/bf01307910
|View full text |Cite
|
Sign up to set email alerts
|

Race, class and support for police use of force

Abstract: Abstract. Analysis of attitudes toward the use of force by police finds that in 1991 70% of white and 43% of black respondents "approve of a policeman striking an adult male citizen" under some circumstances. A pattern is found of groups with greater power, status and advantages (whites, males, the more educated and the more wealthy) being more likely to favor police use of force than are less privileged groups. Other factors found to have significant net relationships with support for police violence include,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 10 publications
1
37
1
10
Order By: Relevance
“…Moreover, religious fundamentalists tend to approve of corporal punishment for children (Ellison, Bartowski, and Segal, ), an orientation that suggests approval of the use of violence to control those who violate rules. Previous studies have shown that religious fundamentalists tend to express greater support for police use of force (Arthur and Case, ; Barkan and Cohn, ).…”
Section: Explaining Support For Police Use Of Forcementioning
confidence: 99%
“…Moreover, religious fundamentalists tend to approve of corporal punishment for children (Ellison, Bartowski, and Segal, ), an orientation that suggests approval of the use of violence to control those who violate rules. Previous studies have shown that religious fundamentalists tend to express greater support for police use of force (Arthur and Case, ; Barkan and Cohn, ).…”
Section: Explaining Support For Police Use Of Forcementioning
confidence: 99%
“…Racial groups have been shown to differ greatly in their support for the death penalty (e.g., Barkan and Cohn, ; Unnever and Cullen, , ). Researchers have suggested that the gap in level of support between Whites and Blacks has widened insofar as minorities perceive themselves to be the disproportionate recipient of the most severe criminal justice sanctions (Arthur and Case, ; Jacobs, Carmichael, and Kent, ; Keil and Vito, ; Young, ). Increased awareness of the disproportionate use of the death penalty on minority offenders may have led to declines in support for the death penalty among non‐Whites but also for some Whites.…”
Section: The Current Studymentioning
confidence: 99%
“…Overall, racial minorities have less power in American society. Studies that have specifically investigated attitudes toward police use of force have found that minorities generally disapprove of police violence (Arthur 1993;Arthur and Case 1994;Cullen et al 1996). Other studies have indicated that minorities feel the criminal justice system is biased in general, and that minorities are unable to receive fair treatment from police and the larger judicial system.…”
Section: Racementioning
confidence: 99%